2014
DOI: 10.1002/ase.1429
|View full text |Cite
|
Sign up to set email alerts
|

Human cadavers Vs. multimedia simulation: A study of student learning in anatomy

Abstract: Multimedia and simulation programs are increasingly being used for anatomy instruction, yet it remains unclear how learning with these technologies compares with learning with actual human cadavers. Using a multilevel, quasi-experimental-control design, this study compared the effects of "Anatomy and Physiology Revealed" (APR) multimedia learning system with a traditional undergraduate human cadaver laboratory. APR is a model-based multimedia simulation tool that uses high-resolution pictures to construct a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
11

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 24 publications
3
85
0
11
Order By: Relevance
“…case seminars with organs and autopsies, seemed to help students develop connections and place the theoretical knowledge in a relevant context. The opportunity to examine organs, visually and tactile, may be important for learning, which has also been found by other researchers (Preece et al 2013, Saltarelli et al 2014). …”
Section: Influence Of the Learning Environmentsupporting
confidence: 71%
See 1 more Smart Citation
“…case seminars with organs and autopsies, seemed to help students develop connections and place the theoretical knowledge in a relevant context. The opportunity to examine organs, visually and tactile, may be important for learning, which has also been found by other researchers (Preece et al 2013, Saltarelli et al 2014). …”
Section: Influence Of the Learning Environmentsupporting
confidence: 71%
“…Furthermore, tactile experiences seem to be important for learning in medicine. Students seem to learn more when participating in anatomical dissections or using physical anatomical models rather than virtual models (Preece et al 2013, Saltarelli et al 2014. The importance of seeing and touching real organs when learning pathology has also been reported by Weurlander and colleagues (2009).…”
Section: Students' Experiences Of Understandingmentioning
confidence: 65%
“…The obtained data supports the role of eBook technology in modern anatomy curriculum as a useful adjunct to traditional methods. Saltarelli et al [5] built an experimental software system called "Anatomy and Physiology Revealed" (APR), which is a model-based multimedia simulation tool that uses high-resolution pictures to construct a prosected cadaver, and also provides animations showing the function of specific anatomical structures. Researches show that this software is helpful to improve students' cognition degree of knowledge.…”
Section: State Of the Artmentioning
confidence: 99%
“…Basic e-book versions of traditional anatomy textbooks and atlases use static 2D images. In contrast, many CAL resources provide fadable, layered 2D images allowing virtual dissection (Saltarelli et al, 2014) and/or rotatable 3D images (with or without stereoscopic viewing) (Cornwall and Pollard, 2012;Lewis et al, 2014b;Temkin et al, 2006;Yammine and Violato, 2015). A meta-analysis of 36 studies found that 3D images are superior to 2D in spatial and factual anatomical knowledge, satisfaction and perceived effectiveness (Yammine and Violato, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 36 studies found that 3D images are superior to 2D in spatial and factual anatomical knowledge, satisfaction and perceived effectiveness (Yammine and Violato, 2015). Comparing 3D CAL resources with dissection has produced mixed results, either similar performance on spatial anatomical knowledge (Codd and Choudhury, 2011) or worse performance from 3D CAL resources on identification and explanation questions (Saltarelli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%